Análise econométrica dos preços de madeira de eucalipto e resina de pinus e avaliação econômica alternativa para seus projetos - Vieira, João Paulo Viel (Universidade Federal de São Carlos, 2016)
Historically, in Brazil, small farms were used as a source of livelihood or recreation areas, currently also as a way to supplement income or a way to ensure security. These small investors, for lack of knowledge often end up leaving to make economic analyzes and market behavior before engaging in forestry projects. The work aimed to study the behavior of prices of eucalyptus wood and gum rosin of Pinus elliottii and the economic viability of traditional manner and project alternative that aim to produce these two products. For this we used econometric univariate models to forecast the prices of the products studied, finding a maximum error of 4.65%. Conditional heteroscedasticity models were applied to predict the volatility of resin prices and eucalyptus wood prices for the process, which were 5.72% and 4.28% per month respectively. The bootstrap simulation method was used to determine the volatility of pine resin prices, and obtained a value of 8.76%. The theory of real options was used to determine the economic viability of projects, had their results compared with traditional methodologies. Furthermore, the volatility obtained by the conditional heterocedasticity model and the bootstrap alternative approaches were applied to this theory, no difference in volatility analysis obtained by the bootstrap method. It is indicated greater care in feasibility studies for forest projects across the long term that they demand and due to different results according to each methodology as demonstrated in this work.
Econometric analysis of prices of eucalyptus wood and pine resin and alternative economic evaluation for your projects
Keywords: Pinus elliottii - Aspectos econômicos; Slash pine - Economic aspects; Resina de pinheiro; Pine gum; Opções reais; Volatilidade; Bootstrap; GARCH; ARIMA; Real options; Volatility; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS